‘‘Motherhood’’ in the Context of Living With Breast Cancer - Fisher, C.; O'Connor, Moira (Lippincott Williams & Wilkins, 2012)
Background: Breast cancer is the most commonly diagnosed cancer among women in Western Australia, with negative psychological impacts exacerbated for younger women. Many women survive 5 years following diagnosis, suggesting more young women and their families will be living with its ongoing effects for longer periods. Diagnosis and treatment impact a woman’s identity as a mother, but limited research exists from the women’s perspective. Objective: The aim of the study was to explore the impact of breast cancer on the identities of young women as “mothers.” Methods: A qualitative research design using conversational in-depth interviews and guided by a social constructivist paradigm was used. In-depth interviews were undertaken with 8 young women who were living with breast cancer and had dependent children. Interviews were audiotaped, transcribed, and analyzed. Results: Biographical disruption as described by Bury provided the analytical framework for interpretation of data. Four themes, “diagnosis and disruption,” “maintaining normality,” “continuing the mothering role,” and “experiencing survivorship,” reflect women’s experiences of identity reconstruction in the context of living with breast cancer. Conclusions: A breast cancer diagnosis precipitates complex changes in a woman’s identity as a mother. A woman’s postdiagnosis identity invariably integrates a changed prediagnosis identity and that of “breast cancer patient” and “survivor.” The relationship between the 3 is dynamic and in constant tension. Implications for Practice: Routine practice should include acknowledgement that an identity as mother exists alongside “patient.” Questions to women about children and any concerns and issues they may have should also be routine.